2011
DOI: 10.1148/radiol.11101344
|View full text |Cite
|
Sign up to set email alerts
|

Is Functional MR Imaging Assessment of Hemispheric Language Dominance as Good as the Wada Test?: A Meta-Analysis

Abstract: Functional MR imaging provides an excellent, noninvasive alternative for language lateralization and should be considered for the initial preoperative assessment of hemispheric language dominance. Further research may help determine which functional MR methods are most accurate for specific patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 40 publications
7
75
0
Order By: Relevance
“…The sensitivity of fMRI lateralization to the left hemisphere compares well with other studies; for example, a recent metaanalysis 13 of 23 studies showed the sensitivity for detection of left dominance to be 88.1% (95% confidence interval, 87.0 -89.2%). However, the authors showed the sensitivity for nonleft dominance to be 83.5% (95% confidence interval, 80.2%-86.7%), which is substantially higher than our value of 69%.…”
Section: Discussionsupporting
confidence: 73%
“…The sensitivity of fMRI lateralization to the left hemisphere compares well with other studies; for example, a recent metaanalysis 13 of 23 studies showed the sensitivity for detection of left dominance to be 88.1% (95% confidence interval, 87.0 -89.2%). However, the authors showed the sensitivity for nonleft dominance to be 83.5% (95% confidence interval, 80.2%-86.7%), which is substantially higher than our value of 69%.…”
Section: Discussionsupporting
confidence: 73%
“…1 The same holds true for determining the language-dominant hemisphere before neurosurgery. 2 BOLD fMRI is a valuable neuroimaging tool for assessing language functions noninvasively, namely, for localizing essential language areas and thereby assessing their spatial relationship to brain tumors, and for determining the languagedominant hemisphere, by analyzing language lateralization. [3][4][5][6][7][8] fMRI language lateralization also has the potential to allow for the study of brain plasticity in different pathologic states, such as epilepsy and stroke.…”
mentioning
confidence: 99%
“…[5][6][7] In a meta-analysis of 23 studies including 442 epilepsy patients, the sensitivity and specificity of fMRI for atypical language dominance, compared with the Wada test, were 83.5% and 88% respectively. [8] The task of localising cortical areas critical to language is more challenging. Electrocortical stimulation (ECS) remains the most reliable technique, even with the advancements in fMRI.…”
mentioning
confidence: 99%